Pengaruh Daya Tarik, Direct Marketing Dan Keamanan Terhadap Kepuasan Konsumen PT. Bina Mulia Perkasa - Harmadi awei; David Humala Sitorus (eCo-Buss, 2024)
PT. Bina Mulia Perkasa as a company in Batam City which is engaged in the sale of building materials. In this case PT. Bina Mulia Perkasa feels the intense competition in the field of building materials. The strategy of each company is different so that it will become a characteristic and competitive advantage for every building materials company. Therefore, PT. Bina Mulia Perkasa must be able to compete with similar companies. The strategy used by PT. Bina Mulia Perkasa to satisfy consumers by covering attractiveness, direct marketing and security. The purpose of this research is to find out how attractiveness, direct marketing and security can influence consumer satisfaction at PT. Bina Mulia Mighty. The method uses descriptive and quantitative, with a population of 211, the sample is based on the slovin formula with a total of 138 respondents and can use probability sampling with the simple random sampling technique. Data analysis techniques through data quality testing, classical assumption testing, influence testing and hypothesis testing. The findings of the research results can be concluded that attractiveness, direct marketing and security can have a positive and significant effect partially and simultaneously on customer satisfaction at PT. Bina Mulia Mighty.